Mars' Ionospheric Interaction With Comet C/2013 A1 Siding Spring's Coma at Their Closest Approach as Seen by Mars Express. Issue 1 (16th January 2020) - Sánchez–Cano, Beatriz; Lester, Mark; Witasse, Olivier; Morgan, David D.; Opgenoorth, Hermann; Andrews, David J.; Blelly, Pierre‐Louis; Cowley, Stanley W. H.; Kopf, Andrew J.; Leblanc, François; Espley, Jared R.; Cardesín‐Moinelo, Alejandro
Abstract: On 19 October 2014, Mars experienced a close encounter with Comet C/2013 A1 Siding Spring. Using data from the Mars Advanced Radar for Subsurface and Ionosphere Sounding (MARSIS) on board Mars Express (MEX), we assess the interaction of the Martian ionosphere with the comet's coma and possibly magnetic tail during the orbit of their closest approach. The topside ionospheric electron density profile is evaluated from the altitude of the peak density of the ionosphere up to the MEX altitude. We find complex and rapid variability in the ionospheric profile along the MEX orbit, not seen even after the impact of a large coronal mass ejection. Before closest approach, large electron density reductions predominate, which could be caused either by comet water damping or comet magnetic field interactions. After closest approach, a substantial electron density rise predominates. Moreover, several extra topside layers are visible along the whole orbit at different altitudes, which could be related to different processes as we discuss. Plain Language Summary: The comet Siding Spring made a single flyby through the solar system in October 2014, passing close to Mars on 19 October 2014, at only one third of the Earth‐Moon distance. For about 10 hr, the Martian ionosphere (upper atmosphere) was in touch with the cometary coma (also called cometary atmosphere). In this work, we use data from the Mars Express mission to evaluate the behavior of the ionosphere of Mars at the comet closest approach. We find that the Martian ionosphere suffered a quick and complex variability with large density increases and decreases every few kilometers. This variability was caused by the presence of the comet, and we discuss different processes that could have occurred. Key Points: Large and rapid Martian ionospheric variability is observed during the closest approach with comet Siding Spring The Martian topside ionosphere is more variable after the comet Siding Spring flyby than after a coronal mass ejection arrived at Mars Cometary water, dust, and comet induced magnetic field seem to be equally responsible for the large ionospheric density variability